Fading and Color Reproducibility of Nipple–Areola Tattoos in Asian Patients - Yamamoto, Mao; Mori, Hiroki; Akiyama, Masako; Okazaki, Mutsumi (Archives of Plastic Surgery, 2024)
Background The purpose of this study was to clarify fading, red, green, and blue values (RGB) change, and color reproducibility for nipple–areola complex (NAC) tattoos.Methods NAC tattooing was performed on 60 sites in 59 Japanese patients prospectively. The evaluation was assessed using digital photo, Casmatch standardization, and RGB and luminance values preoperatively, immediately after, 1 week, 1, 3, 6, and 12 months after tattooing. RGB and luminance values changes over time, time-adjusted fading rate, and the rate of luminance at 12 months were calculated. In color reproducibility study (n = 34), RGB values after 12 months were compared with the color sample about dark/reddish and light/less reddish pigments.Results RGB varied widely from immediately after to 1 month after tattooing. For RGB and luminance, significant differences were seen between pre and immediate after, 1 and 3 months, 3 and 6 months, and 6 and 12 months. In G values, significant differences were seen between all neighboring points. The fading rate tended to decrease as time progresses, but was not significant, that is, fading continued even between 6 and 12 months. Luminance was 9% brighter than contralateral NAC at 12 months. Color reproducibility tended to be higher with dark/reddish pigments, despite no significant differences.Conclusion The fading rate of tattooed NACs tended to decrease as time progresses, but fading still occurs between 6 and 12 months. Luminance was 9% brighter than contralateral NAC at 12 months after.
Keywords: nipple; tattoo; breast reconstruction; NAC